Effect of tunneling conductivity of CNTs on the EMI shielding effectiveness of nanocomposite in the C-band - Modanwal Rajnish P.; Gupta Madhur; Kundalwal Shailesh I. (Journal of the Mechanical Behavior of Materials)
In the present work, the electromagnetic interference (EMI) shielding effectiveness (SE) of carbon nanotube-reinforced nanocomposite (CNRC) is investigated by using an analytical approach. CNRC is composed of a polypyrrole matrix and carbon nanotubes (CNTs). The effect of the tunneling conductivity of CNTs on the EMI SE is studied quantitively, at different weight percentages (wt%) of CNTs, by varying the aspect ratio of CNTs, CNT-matrix interphase thickness, and waviness of CNTs. We observed that the SE is significantly influenced by the wt% of CNTs and the thickness of CNRC in the frequency range of 4.2–8.2 GHz (C-band). To support the theoretical investigations and understand the shielding mechanism of CNRC, a finite-element model is derived using commercially available software Ansys HFSS. The outcomes of both models are in good agreement. In addition, our investigation reveals that the electrical conductivity of CNRC is significantly improved with the increased wt% and aspect ratio of CNTs, as well as with increased interphase thickness. However, it degrades as the waviness of CNT increases. Our results suggest that the raised tunneling conductivity of CNTs improves the EMI SE of CNRC significantly. For the sake of greater clarity, the quantitative relative performance of the CNRC is also presented. Our foundational study highlights an opportunity to develop effective and lightweight CNT-based nanocomposites, which can be used in EMI SE applications.